Electromagnetic wave shielding material, covering material or exterior material, and electrical device or electronic device
By using a laminated structure of a non-magnetic resin layer, a non-magnetic metal layer and/or a ferromagnetic layer in the electromagnetic wave shielding material, the anisotropy value during rupture is controlled, and the problem of difficult to maintain the shape of the material after processing is solved, and excellent shape retention is achieved.
Patent Information
- Application Number
- CN202380050518.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2022-11-08
- Filing Date
- 2023-10-20
- Publication Date
- 2025-03-11
AI Technical Summary
The conventional electromagnetic wave shielding material is difficult to maintain its shape after processing, especially after applying a rebound force, and the height of the molded body is difficult to maintain, resulting in poor shape retention.
An electromagnetic wave shielding material including a laminate is used, which consists of a non-magnetic resin layer, a non-magnetic metal layer and/or a ferromagnetic layer. Through a specific laminate structure and material combination, the anisotropy (Rc) value during rupture is controlled to be 0 or less or more to improve shape retention.
By optimizing the structure and material combination of the laminated body, the shape retention of the electromagnetic wave shielding material is significantly improved, so that it can maintain its molded shape more easily after processing.
Smart Images

Figure CN119605322A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an electromagnetic wave shielding material, a covering material or an exterior material, and an electric device or an electronic device. Background Art
[0002] In environmentally friendly vehicles such as electric vehicles and hybrid vehicles equipped with secondary batteries, the DC current generated by the installed secondary batteries is often converted into AC current through an inverter, and the required electricity is supplied to the AC motor to obtain driving force. The conversion operation of the inverter will cause the generation of electromagnetic waves.
[0003] In addition, electromagnetic waves are also emitted by a variety of electrical and electronic devices, including not only automobiles but also communication devices, displays, and medical equipment. Electromagnetic waves may cause malfunctions of precision equipment and may also have an impact on the human body.
[0004] It is known that, typically in the high frequency region (above 1 MHz), a conductive layer such as copper shows good shielding properties against electromagnetic waves. On the other hand, in the low frequency region (less than 1 MHz), if only a conductive layer such as copper is used, the shielding properties against electromagnetic waves are low, so an electromagnetic wave shielding material formed by alternating and stacking a magnetic layer with excellent magnetic permeability and a conductive layer shows good shielding properties against electromagnetic waves.
[0005] For example, in Patent Document 1, the following technology is proposed.
[0006] "A noise suppression sheet, characterized in that it is a noise suppression sheet for suppressing noise below 1 MHz, comprising: a magnetic layer (A1) and a magnetic layer (A n ) of n magnetic layers, a noise suppression layer having at least (n-1) conductive layers,
[0007] The magnetic layers and the conductive layers are stacked alternately.
[0008] In any of the magnetic layers, X represented by the following formula (1): i is 1 or more,
[0009] The X of each magnetic layer i The total is 4 or more but less than 15.
[0010] For any of the above conductive layers, in a magnetic shielding property measurement using a KEC method, a proportionality constant obtained by linearly approximating the shielding property at 0.2 to 1 MHz is 4 or more:
[0011] X i =√μ′ i ×√t i Formula (1)
[0012] wherein n is an integer greater than 2, i is an integer greater than 1 and less than n,
[0013] μ′ i The magnetic layer (A i ) Relative permeability at 1MHz, t i The magnetic layer (A i ) film thickness [mm]. "
[0014] Prior art literature
[0015] Patent Literature
[0016] Patent Document 1: Japanese Patent Application Publication No. 2021-028940 Summary of the invention
[0017] Technical problem to be solved by the invention
[0018] It is worth mentioning that there are cases where electromagnetic wave shielding materials are used as outer packaging materials and are drawn to match the shape of housings or electronic components. However, there is the following technical problem: even if a shape having the desired height is formed by drawing, it is difficult to maintain the height of the molded body, that is, it is difficult to maintain the shape because a force (rebound) is applied to the molded body after processing to try to restore it to the shape before processing. In particular, depending on the material, there is a situation where the height is restored to about half of the height just after processing, which becomes a technical problem in industrial production. Therefore, if the shape retention of electromagnetic wave shielding materials can be improved, it will have far-reaching significance in industry. In addition, in Patent Document 1, no attention is paid to the above-mentioned shape retention.
[0019] Therefore, in one embodiment of the present invention, an object is to provide an electromagnetic wave shielding material having excellent shape retainability.
[0020] Solutions to technical problems
[0021] In order to solve the above-mentioned technical problems, the inventors conducted in-depth research and found that the electromagnetic wave shielding material has excellent shape retention by including a laminate, and the laminate has a non-magnetic resin layer, a non-magnetic metal layer and / or a ferromagnetic layer, and the value of the anisotropy (Rc) at rupture shown in the following formula (1) is less than 0 or greater than 1, and created the invention of the following example. [1]
[0023] An electromagnetic wave shielding material comprises a laminate having a non-magnetic resin layer, a non-magnetic metal layer and / or a ferromagnetic layer, wherein:
[0024] The value of the anisotropy (Rc) at the time of rupture represented by the following formula (1) is 0 or less or 1 or more:
[0025]
[0026] Rc: Anisotropy at rupture
[0027] w: Width of the fractured portion of the laminate after tensile test (mm)
[0028] w0: Width of the laminate before tensile test (mm)
[0029] t: Thickness of the broken part of the laminate after tensile test (μm)
[0030] t0: thickness of the laminate before the tensile test (μm). [2]
[0032] The electromagnetic wave shielding material as described in [1], wherein
[0033] The laminated body comprises the non-magnetic metal layer.
[0034] The non-magnetic resin layer is provided on surfaces of both sides of the non-magnetic metal layer. [3]
[0036] The electromagnetic wave shielding material as described in [1] or [2], wherein
[0037] The laminated body comprises the ferromagnetic layer.
[0038] The non-magnetic resin layer is provided on the surfaces of both sides of the ferromagnetic layer. [4]
[0040] The electromagnetic shielding material according to any one of [1] to [3], wherein the non-magnetic metal layer has a thickness of 10 to 200 μm and contains at least one metal having a rupture elongation of 2% or more in the RD direction. [5]
[0042] The electromagnetic shielding material according to any one of [1] to [4], wherein the nonmagnetic metal layer contains at least one selected from copper, copper alloys, aluminum, and aluminum alloys. [6]
[0044] The electromagnetic shielding material according to any one of [1] to [5], wherein the value of the anisotropy (Rc) of the non-magnetic resin layer at break represented by the following formula (2) is 1.0 or more and 10 or less, or -10 or more and 0 or less:
[0045]
[0046] Rc: Anisotropy at rupture
[0047] w: Width of the fractured portion of the non-magnetic resin layer after the tensile test (mm)
[0048] w0: Width of non-magnetic resin layer before tensile test (mm)
[0049] t: Thickness of the fractured portion of the non-magnetic resin layer after the tensile test (μm)
[0050] t0: thickness of the non-magnetic resin layer before the tensile test (μm). [7]
[0052] The electromagnetic shielding material according to any one of [1] to [6], wherein the non-magnetic resin layer contains at least one selected from PET and PC. [8]
[0054] The electromagnetic shielding material according to any one of [1] to [7], wherein the non-magnetic resin layer contains conductive particles and / or conductive fibers. [9]
[0056] A covering material or exterior material for an electric device or an electronic device, comprising the electromagnetic wave shielding material according to any one of [1] to [8].
[10]
[0058] An electrical device or electronic device having the covering material or exterior material as described in [9].
[0059] Effects of the Invention
[0060] According to one embodiment of the present invention, an electromagnetic wave shielding material having excellent shape retainability can be provided. BRIEF DESCRIPTION OF THE DRAWINGS
[0061] Figure 1 (A) to (C) are schematic diagrams for explaining the procedure of the shape retaining property test. DETAILED DESCRIPTION
[0062] Hereinafter, the present invention is not limited to each embodiment, and the components can be modified and embodied within the scope not departing from the gist thereof. In addition, various inventions can be formed by appropriately combining a plurality of components disclosed in each embodiment.
[0063] [1.Electromagnetic wave shielding materials]
[0064] One embodiment of the electromagnetic wave shielding material of the present invention includes a laminate having a nonmagnetic resin layer and a nonmagnetic metal layer and / or a ferromagnetic layer.
[0065] Hereinafter, appropriate methods will be described respectively.
[0066] <Laminated body>
[0067] (Anisotropy at rupture)
[0068] From the perspective of ensuring excellent shape retention, the anisotropy value of the laminate when it is broken is less than 0 or greater than 1. When the electromagnetic wave shielding material is used as an exterior material, it is very important to adjust the balance between the thinning of the thickness in the thickness direction and the shrinkage in the width direction of the laminate from the perspective of ensuring excellent shape retention. Therefore, the following formula (1) is specified for the anisotropy value when it is broken.
[0069] Anisotropy at rupture (Rc) indicates the degree of deformation in the thickness direction and the width direction of the plate when the same elongation is given to the plate-like sample. When the value of Rc is greater than 0 and less than 1, it indicates a state in which the width does not change but the thickness becomes smaller after the plate-like sample is processed. When the value of Rc is 1, it indicates a state in which the thickness and width change at the same ratio before and after processing. When the value of Rc is greater than 1, it indicates a state in which the width changes but the thickness does not change after processing. It is known that when a metal monomer is formed by a forming process such as drawing, especially materials such as copper and aluminum that are prone to local elongation (0<Rc<1), they are constantly deformed locally, so they will break and the forming process itself is difficult. In addition, when a composite sheet obtained by mixing and dispersing a metal material and a resin and integrally forming it is formed by a forming process such as drawing, it is known that the material with 0<Rc<1 has poor shape retention. Based on these results, the present inventors found that when metal and resin are laminated, when the Rc value of the laminate is 0 or less or 1 or more, local deformation is suppressed, molding processing becomes easier, and the shape after molding is easily maintained, thereby obtaining the present invention.
[0070]
[0071] Rc: Anisotropy at rupture
[0072] w: Width of the fractured portion of the laminate after tensile test (mm)
[0073] w0: Width of the laminate before tensile test (mm)
[0074] t: Thickness of the broken part of the laminate after tensile test (μm)
[0075] t0: thickness of the laminate before tensile test (μm)
[0076] In order to calculate the above formula (1), the width and thickness of the laminate before and after the tensile test are respectively determined, and the ratio of the width strain to the thickness strain is determined based on the following formulas (3) and (4). Thus, the value of the anisotropy (Rc) at rupture can be determined.
[0077]
[0078] w: Width of the fractured portion of the laminate after tensile test (mm)
[0079] w0: Width of the laminate before tensile test (mm)
[0080] t: Thickness of the broken part of the laminate after the tensile test (μm)
[0081] t0: thickness of the laminate before tensile test (μm)
[0082] ε w : Width strain
[0083] ε t : Thickness strain
[0084]
[0085] ε w : Width strain
[0086] ε t : Thickness strain
[0087] Rc: Anisotropy at fracture
[0088] In addition, the method of measuring the width strain and the thickness strain in the tensile test is as follows.
[0089] For the evaluation sample, a precision tool is used to cut the laminate into a width of 12.7 mm, and a cutter or scissors are used to cut it into a length of 10 cm (100 mm). Next, a desktop precision universal testing machine (Autograph AGS-X, manufactured by Shimadzu Corporation) is used to fix the evaluation sample in a manner such that each end of the length direction of the evaluation sample is clamped by a clamp (chuck) as a test fixture with a length of 20 mm and an initial distance between the chucks of 60 mm. Next, the evaluation sample is stretched along the length direction (long side direction) at a tensile speed of 50 mm / min using the desktop precision universal testing machine. Then, when the evaluation sample is broken at 2 locations, the tensile test is terminated. Based on the above formulas (3) and (4), the width strain and thickness strain of the evaluation sample are calculated according to the width and thickness of the evaluation sample before and after the tensile test, and the value of Rc is calculated.
[0090] As an example of a method for measuring the thickness required to calculate the value of Rc, it can be measured using a constant pressure thickness tester (THICKNESS METER B-1, manufactured by Toyo Seiki Seisaku-sho) in accordance with Method A in JIS K 6250:2019. It should be noted that the diameter of the indenter can be selected to be 5 mm, and the pressure of the indenter can be set to 1.22 N for measurement. In addition, as an example of a method for measuring the width, it can be fixed on thick paper with tape in a manner that the ruptured portion does not curl, and then measured using a caliper. Regarding the width after the rupture, the width is measured in a direction perpendicular to the length direction for the portion of the necking that is visually the smallest width produced near the rupture.
[0091] The laminate can be a structure in which a non-magnetic metal layer and / or a ferromagnetic layer are closely laminated via a non-magnetic resin layer.
[0092] For example, when the laminate has a non-magnetic metal layer, it is preferred that a non-magnetic resin layer is provided on the surface of both sides of the non-magnetic metal layer. It is preferred to select a structure in which the surface of both sides of the non-magnetic metal layer and the non-magnetic resin layer are closely laminated, in terms of improving the ductility of the non-magnetic metal layer and improving the shape retention of the laminate. As a non-magnetic metal layer, metal foils such as copper or aluminum are prone to local elongation, so by using a non-magnetic resin layer that is relatively difficult to locally stretch to clamp, it is possible to alleviate the local concentration of stress. Thus, it is possible to ensure excellent shape retention.
[0093] For example, when the laminate has a ferromagnetic layer, it is preferred that a non-magnetic resin layer is provided on the surfaces of both sides of the ferromagnetic layer. The presence of the non-magnetic resin layer can alleviate the local concentration of stress, thereby ensuring excellent shape retention.
[0094] It should be noted that, when there is a non-magnetic metal layer on the surface of one side of the ferromagnetic layer, preferably, there is a non-magnetic resin layer on the surface of the other side of the ferromagnetic layer opposite to the non-magnetic metal layer, and there is a non-magnetic resin layer on the surface of the other side of the non-magnetic metal layer opposite to the ferromagnetic layer. By indirectly sandwiching the non-magnetic metal layer with a non-magnetic resin layer, not only can the local concentration of stress be alleviated, but also it can be expected that the electromagnetic wave shielding characteristics are improved and the shape retention obtained by having a layer with a high Young's modulus is good. In addition, the ferromagnetic layer is more preferably a composite sheet (an integrally formed object mixed and dispersed with a magnetic metal material and a resin). Thus, it is possible to ensure excellent shape retention.
[0095] (Laminated structure)
[0096] Examples of the laminated structure of the laminate are listed below.
[0097] (1) When the laminated structure is composed of two layers, for example, non-magnetic resin layer / ferromagnetic layer and non-magnetic resin layer / non-magnetic metal layer are mentioned.
[0098] (2) When the stacked structure as a stacked body consists of three layers, for example, the following can be listed: non-magnetic resin layer / ferromagnetic layer / non-magnetic resin layer, non-magnetic resin layer / non-magnetic metal layer / non-magnetic resin layer, non-magnetic resin layer / ferromagnetic layer / non-magnetic metal layer, non-magnetic resin layer / non-magnetic metal layer / ferromagnetic layer, ferromagnetic layer / non-magnetic resin layer / ferromagnetic layer, ferromagnetic layer / non-magnetic resin layer / non-magnetic metal layer.
[0099] (3) When the stacked structure as a stacked body consists of four layers, for example, the following can be listed: non-magnetic resin layer / ferromagnetic layer / non-magnetic resin layer / ferromagnetic layer, non-magnetic resin layer / non-magnetic metal layer / non-magnetic resin layer / non-magnetic metal layer, non-magnetic resin layer / non-magnetic metal layer / ferromagnetic layer / non-magnetic resin layer, non-magnetic resin layer / ferromagnetic layer / non-magnetic metal layer, non-magnetic resin layer / non-magnetic metal layer / ferromagnetic layer / non-magnetic resin layer, non-magnetic resin layer / ferromagnetic layer / non-magnetic metal layer, non-magnetic resin layer / non-magnetic metal layer / non-magnetic resin layer / ferromagnetic layer.
[0100] (4) When the stacked structure as a stacked body consists of 5 layers, for example, the following can be listed: non-magnetic resin layer / ferromagnetic layer / non-magnetic resin layer / ferromagnetic layer / non-magnetic resin layer, non-magnetic resin layer / non-magnetic metal layer / non-magnetic resin layer / non-magnetic metal layer / non-magnetic resin layer, non-magnetic resin layer / non-magnetic metal layer / ferromagnetic layer / non-magnetic metal layer / non-magnetic resin layer, non-magnetic metal layer / non-magnetic resin layer / ferromagnetic layer / non-magnetic metal layer / non-magnetic resin layer, non-magnetic metal layer / non-magnetic resin layer / ferromagnetic layer / non-magnetic resin layer / non-magnetic metal layer.
[0101] (5) When the stacked structure as a stacked body consists of 6 layers, for example, the following can be listed: non-magnetic resin layer / ferromagnetic layer / non-magnetic resin layer / ferromagnetic layer / non-magnetic resin layer / ferromagnetic layer, non-magnetic resin layer / non-magnetic metal layer / non-magnetic resin layer / non-magnetic metal layer / non-magnetic resin layer / non-magnetic metal layer, non-magnetic resin layer / non-magnetic metal layer / ferromagnetic layer / non-magnetic metal layer / ferromagnetic layer / non-magnetic resin layer, non-magnetic resin layer / non-magnetic metal layer / non-magnetic metal layer / ferromagnetic layer / non-magnetic resin layer, non-magnetic resin layer / non-magnetic metal layer / non-magnetic resin layer / ferromagnetic layer / non-magnetic metal layer / non-magnetic resin layer.
[0102] In one embodiment, a "non-magnetic resin layer" of one layer also includes a layer formed by laminating multiple non-magnetic resin layers without a ferromagnetic layer or a non-magnetic metal layer. That is, in one embodiment, multiple non-magnetic resin layers laminated without a ferromagnetic layer or a non-magnetic metal layer are regarded as a single non-magnetic resin layer.
[0103] In addition, a non-magnetic resin layer on which a bonding layer is laminated without a ferromagnetic layer or a non-magnetic metal layer being interposed is regarded as one non-magnetic resin layer.
[0104] The more the number of non-magnetic resin layers, non-magnetic metal layers, and ferromagnetic layers are stacked, the easier it is to improve the shielding properties. However, increasing the number of stacking will increase the workload and thus lead to an increase in manufacturing costs. In addition, if the number of stacking exceeds the specified number, the effect of improving the shielding properties tends to be saturated. Therefore, the number of non-magnetic resin layers in the electromagnetic wave shielding material can be more than one layer, and the number of non-magnetic metal layers and / or ferromagnetic layers can be more than one layer.
[0105] (Elongation at break)
[0106] From the viewpoint of processability, the elongation at break of the laminate in the RD direction is preferably 10% or more, more preferably 30% or more. However, in consideration of a reasonable elongation at break, the elongation at break in the RD direction is typically 300% or less, more typically 250% or less.
[0107] In addition, from the viewpoint of processability, the elongation at break of the laminate in the TD direction is preferably 20% or more, more preferably 30% or more. However, considering a reasonable elongation at break, the elongation at break in the TD direction is typically 300% or less, more typically 250% or less.
[0108] The RD direction refers to the roller conveying direction of the non-magnetic resin layer and / or the non-magnetic metal layer, and the TD direction refers to the direction rotated 90° from the RD direction.
[0109] The method for measuring the elongation at break in each direction is as follows in accordance with JIS K7127:1999.
[0110] For the evaluation sample, the laminate is cut into a width of 12.7mm using a precision tool, and cut into a length of 10cm (100mm) using a cutter or scissors. At this time, when the elongation at break in the RD direction of the laminate is measured, the RD direction of the laminate is made in a manner that the length direction of the evaluation sample is made. In addition, when the elongation at break in the TD direction of the laminate is measured, the TD direction of the laminate is made in a manner that the length direction of the evaluation sample is made. Using a test fixture of a desktop precision universal testing machine (オートグラフAGS-X, manufactured by Shimadzu Corporation), the length of each end of the length direction of the evaluation sample is clamped by a clamp (chuck) as a test fixture, and the distance between the initial chucks is 60mm, respectively, The evaluation sample is fixed. Next, the tensile speed of the desktop precision universal testing machine is 50mm / min, and the evaluation sample is stretched along the length direction (length direction). Then, when the evaluation sample is broken at 2 places, the tensile test is ended. The value obtained by dividing the length displacement after deformation by the length before deformation was expressed as a percentage and was taken as breaking elongation (%).
[0111] (thickness)
[0112] From the viewpoint of shape retention, the thickness of the laminate is preferably 10 μm or more, more preferably 20 μm or more, and even more preferably 30 μm or more. However, from the viewpoint of stress applied to the molded portion of the laminate formed during processing, the thickness of the laminate is preferably 800 μm or less, more preferably 700 μm or less, and even more preferably 600 μm or less.
[0113] The thickness of the laminate can be measured by a constant pressure thickness tester (THICKNESS METER B-1, manufactured by Toyo Seiki Seisaku-sho) in accordance with Method A of JIS K 6250: 2019. The diameter of the indenter is 5 mm, and the pressure on the indenter is 1.22 N.
[0114] (Layering method)
[0115] As a lamination method of a non-magnetic resin layer, a ferromagnetic layer or a non-magnetic metal layer, an adhesive can be used between the non-magnetic resin layer and the ferromagnetic layer or between the non-magnetic resin layer and the non-magnetic metal layer, or the non-magnetic resin layer can be thermocompressed to the ferromagnetic layer or the non-magnetic metal layer without using an adhesive. A method of simply overlapping without using an adhesive can also be adopted, but if the integrity of the electromagnetic wave shielding material is taken into account, at least the end (for example, each side when the shielding material is a square) is joined by a tape or an adhesive or by thermocompression. However, based on the point that no additional heat is applied to the ferromagnetic layer, an adhesive is preferably used. There is no particular limitation as an adhesive, and acrylic resin systems, epoxy resin systems, polyurethane systems, polyester systems, silicone resin systems, vinyl acetate systems, styrene butadiene rubber systems, nitrile rubber systems, phenolic resin systems, cyanoacrylate systems, etc. can be cited. Based on the reasons of ease of manufacture and cost, polyurethane systems, polyester systems, and vinyl acetate systems are preferred.
[0116] <Non-magnetic resin layer>
[0117] The non-magnetic resin layer includes a resin composition in which no anti-magnetic or paramagnetic body is shown. As a non-magnetic resin layer, the greater the difference in resistance with the ferromagnetic layer or the non-magnetic metal layer, the more preferred it is in terms of obtaining excellent electromagnetic wave shielding properties. In order to produce a larger difference in resistance, it is necessary that the relative dielectric constant of the non-magnetic resin layer is small, specifically preferably 10 (value at 20°C. The same below.) or less, more preferably 5.0 or less, and even more preferably 3.5 or less. In principle, the relative dielectric constant will not be less than 1.0. The materials that can be purchased are usually as low as about 2.0, and even if they are lower and closer to 1.0, the improvement in shielding properties is limited. On the other hand, the material itself is special and expensive. Considering the compatibility of cost and shielding properties, the relative dielectric constant is preferably above 2.0, and more preferably above 2.2.
[0118] As the material constituting the non-magnetic resin layer, synthetic resin is preferred based on the viewpoint of processability. In addition, as the material constituting the non-magnetic resin layer, a film-like material can be used. Fiber-reinforced materials such as carbon fiber, glass fiber and aramid fiber can be mixed into the non-magnetic resin layer. As the synthetic resin, based on the viewpoint of easy purchase and molding processability, polyesters such as PET (polyethylene terephthalate), PC (polycarbonate), PEN (polyethylene naphthalate) and PBT (polybutylene terephthalate), olefin resins such as polyethylene and polypropylene, polyamide, polyimide, liquid crystal polymer, polyacetal, fluororesin, polyurethane, acrylic resin, epoxy resin, silicone resin, phenolic resin, melamine resin, ABS resin, polyvinyl alcohol, urea resin, polyvinyl chloride, polystyrene, styrene butadiene rubber, etc., among which, based on the viewpoint of tensile strength and ductility, PET, PC, polyamide and polyimide are preferred. In addition, as synthetic resins, polyurethane rubber, chloroprene rubber, silicone rubber, fluororubber, styrene-based, olefin-based, vinyl chloride-based, urethane-based, amide-based, and other elastomers can also be used. Among them, polyimide, polybutylene terephthalate, polyamide, polyurethane, etc., which can be easily bonded to metal foil by thermal compression bonding, can be preferably used. The non-magnetic resin layers used in the laminate can all be composed of the same resin material, or different resin materials can be used for each layer.
[0119] In another embodiment, the non-magnetic resin layer may contain conductive particles and / or conductive fibers. As the metal type of the conductive particles and conductive fibers, known metals can be used as long as they have good conductivity, for example, copper, copper alloys, aluminum, aluminum alloys, carbon, etc.
[0120] In this case, the mass ratio of the resin to the conductive particles and conductive fibers is, for example, 70:30 to 1:99.
[0121] The surface of the non-magnetic resin layer may be subjected to various surface treatments for the purpose of promoting adhesion with the non-magnetic metal layer or the ferromagnetic layer. For example, by performing a primer or corona treatment on the bonding surface of the resin film as the non-magnetic resin layer and the metal foil as the non-magnetic metal layer, the adhesion between the resin film and the metal foil can be improved.
[0122] (Anisotropy at rupture)
[0123] Based on the viewpoint of shape processability such as deep drawing, the anisotropy value of the non-magnetic resin layer at the time of rupture is preferably greater than 1.0 and less than 10 or greater than -10 and less than 0, and more preferably greater than 1.2 and less than 5 or greater than -5 and less than -0. It should be noted that the following formula (2) is defined for the above-mentioned anisotropy value at the time of rupture. In the following formula (2), the method for measuring the width strain (ln(W / W0)) and the thickness strain (ln(t / t0)) is the same as the method for measuring the anisotropy value of the laminate at the time of rupture described above.
[0124]
[0125] Rc: Anisotropy at rupture
[0126] w: Width of the fractured portion of the non-magnetic resin layer after the tensile test (mm)
[0127] w0: Width of non-magnetic resin layer before tensile test (mm)
[0128] t: Thickness of the fractured portion of the non-magnetic resin layer after the tensile test (μm)
[0129] t0: Thickness of non-magnetic resin layer before tensile test (μm)
[0130] (Elongation at break)
[0131] From the viewpoint of shape processability such as drawing, the elongation at break of the non-magnetic resin layer in the RD direction is preferably 10% or more, more preferably 20% or more, and even more preferably 80% or more. However, considering a reasonable elongation at break, the elongation at break in the RD direction is typically 500% or less, more typically 400% or less.
[0132] In addition, from the viewpoint of shape processability such as drawing, the elongation at break of the non-magnetic resin layer in the TD direction is preferably 10% or more, more preferably 20% or more, and even more preferably 80% or more. However, considering a reasonable elongation at break, the elongation at break in the TD direction is typically 500% or less, more typically 400% or less.
[0133] The method for measuring the elongation at break in each direction is the same as the method for measuring the elongation at break in each direction of the laminate described above.
[0134] (thickness)
[0135] The thickness of the non-magnetic resin layer is not particularly limited. Based on the viewpoint of processability, the total thickness of the non-magnetic resin layer is preferably 40 μm or more, more preferably 50 μm or more, even more preferably 100 μm or more, and even more preferably 200 μm or more. However, based on the viewpoint of cost reduction, the total thickness of the non-magnetic resin layer is preferably 500 μm or less, more preferably 400 μm or less, and even more preferably 300 μm or less.
[0136] In addition, considering the ease of handling, the thickness of each non-magnetic resin layer is preferably 5 μm or more, more preferably 20 μm or more, and even more preferably 25 μm or more. However, if the thickness of each non-magnetic resin layer is too large, the cost becomes high (the cutting processability is poor), so it is preferably 500 μm or less, and more preferably 300 μm or less.
[0137] It should be noted that the method for measuring the thickness of the non-magnetic resin layer is the same as the method for measuring the thickness of the laminated body described above.
[0138] (Thickness of bonding layer)
[0139] The bonding layer is laminated on the surface of the non-magnetic resin layer and contains an adhesive. Considering the formability of stretch molding, etc., an adhesive with lower strength than the resin film is often used as an adhesive. Therefore, when the thickness of the bonding layer is too thick, the improvement of the ductility of the ferromagnetic layer or the non-magnetic metal layer may be hindered by laminating the non-magnetic resin layer having the bonding layer. On the other hand, when the thickness of the bonding layer is too thin, it is difficult to apply the adhesive on the entire interface between the ferromagnetic layer or the non-magnetic metal layer and the non-magnetic resin layer, and unbonded parts may appear. Therefore, the thickness of the bonding layer is preferably 1 μm to 20 μm, more preferably 1 μm to 10 μm, and even more preferably 3 μm to 9 μm. It should be noted that the bonding layer may also contain conductive particles or conductive fibers without hindering the present invention.
[0140] In addition, the method for measuring the thickness of the adhesive layer is the same as the method for measuring the thickness of the laminated body described above.
[0141] <Strong magnetic layer>
[0142] The ferromagnetic layer has electromagnetic wave absorption characteristics, and the relative magnetic permeability at a frequency of 1 MHz is approximately 10 to 50000. The ferromagnetic layer contains a magnetic metal material with a relatively high relative magnetic permeability, for example, a composite sheet and a metal foil obtained by mixing and dispersing the magnetic metal material and a resin and integrally molding the composite sheet are preferred from the viewpoint of processability and lightness.
[0143] The relative magnetic permeability is generally measured as follows: The measurement sample is processed into a ring shape (outer diameter 6.93 to 6.96 mm, inner diameter 3.06 to 3.10 mm) using a press die or the like, and the relative magnetic permeability is measured using a vector network analyzer (ENAE5071C, manufactured by Keysight).
[0144] When the ferromagnetic layer is a composite sheet, the resin contained in the composite sheet includes natural resins and synthetic resins, and synthetic resins are preferred from the viewpoint of processability. Fiber reinforcement materials such as carbon fibers, glass fibers, and aramid fibers can be mixed into these materials.
[0145] As synthetic resins, from the viewpoint of easy purchase and processability, polyesters such as PET (polyethylene terephthalate), PC (polycarbonate), PEN (polyethylene naphthalate) and PBT (polybutylene terephthalate), olefin resins such as polyethylene and polypropylene, polyamide, PI (polyimide), LCP (liquid crystal polymer), polyacetal, fluororesin, polyurethane, acrylic resin, epoxy resin, silicone resin, phenolic resin, melamine resin, ABS resin, polyvinyl alcohol, urea resin, polyvinyl chloride, polystyrene, styrene butadiene rubber, etc. are listed. Among them, PET, PC, PEN, polyamide, and PI are preferred for reasons of processability and cost. In addition, as synthetic resins, polyurethane rubber, chloroprene rubber, silicone rubber, fluororubber, styrene-based, olefin-based, vinyl chloride-based, urethane-based, amide-based, etc. elastomers can also be used. Furthermore, the synthetic resin itself can play the role of an adhesive. There is no particular limitation on the adhesive, and examples thereof include acrylic resins, epoxy resins, polyurethanes, polyesters, silicone resins, vinyl acetates, styrene butadiene rubbers, nitrile rubbers, phenolic resins, and cyanoacrylates. Based on ease of manufacture and cost, polyurethanes, polyesters, and vinyl acetates are preferred.
[0146] The composite sheet can be laminated on a non-magnetic resin layer or a non-magnetic metal layer in a film-like or fibrous form. In addition, the composite sheet can be obtained by coating a mixed composition of an uncured magnetic metal material and a resin on a resin substrate having a peeling layer, curing the mixed composition, and then peeling it from the resin substrate. For example, the composite sheet can also be formed by coating a mixed composition of an uncured magnetic metal material and a resin on the surface of a non-magnetic resin layer or a non-magnetic metal layer or a treatment film described below, and then curing the mixed composition. In addition, for the reason of ease of manufacturing, it is preferred to select a composite sheet that can be attached to the surface of a non-magnetic resin layer or a non-magnetic metal layer or a treatment film described below.
[0147] It should be noted that the mass ratio of the resin to the magnetic metal material in the composite sheet is, for example, 70:30 to 1:99. In addition, the composite sheet may contain conductive particles or conductive fibers other than the magnetic metal material within the scope that does not hinder the present invention. It should be noted that the examples of conductive particles and conductive fibers are the same as the conductive particles and conductive fibers in the non-magnetic resin layer described above.
[0148] When the ferromagnetic layer is in the form of a metal foil, the ferromagnetic layer preferably contains at least one selected from nickel, iron, permalloy (Ni-Fe alloy) and sendust (Fe-Si-Al alloy). These materials have relatively high relative magnetic permeability, so they can gather the magnetic flux components contained in the noise and reduce the spatial magnetic field.
[0149] (Elongation at break)
[0150] From the viewpoint of processability such as deep drawing, the elongation at break of the ferromagnetic layer in the RD direction is preferably 5% or more, more preferably 10% or more. However, considering a reasonable elongation at break, the elongation at break in the RD direction is typically 100% or less, more typically 70% or less.
[0151] In addition, from the viewpoint of processability such as deep drawing, the elongation at break of the ferromagnetic layer in the TD direction is preferably 5% or more, more preferably 10% or more. However, considering a reasonable elongation at break, the elongation at break in the TD direction is typically 100% or less, more typically 70% or less.
[0152] The method for measuring the elongation at break in each direction is the same as the method for measuring the elongation at break in each direction of the laminate described above.
[0153] (thickness)
[0154] The thickness of the ferromagnetic layer is not particularly limited. From the viewpoint of electromagnetic wave shielding, the total thickness of the ferromagnetic layer is preferably 10 μm or more, more preferably 15 μm or more, even more preferably 20 μm or more, even more preferably 25 μm or more, and even more preferably 30 μm or more. However, from the viewpoint of cost reduction, the total thickness of the ferromagnetic layer is preferably 500 μm or less, more preferably 300 μm or less, and even more preferably 200 μm or less.
[0155] In one embodiment, from the viewpoint of stress applied to the molded portion of the laminate formed during processing, the thickness of each ferromagnetic layer is preferably 5 μm or more, more preferably 10 μm or more, even more preferably 20 μm or more, even more preferably 25 μm or more, further preferably 30 μm or more, and even more preferably 35 μm or more. However, if the thickness of each ferromagnetic layer is too thick, the cost will increase, so it is preferably 100 μm or less.
[0156] It should be noted that the method for measuring the thickness of the ferromagnetic layer is the same as the method for measuring the thickness of the laminated body described above.
[0157] In one embodiment, when forming a plurality of ferromagnetic layers, all ferromagnetic layers may be made of the same material, or different materials may be used for each layer. In addition, all ferromagnetic layers may have the same thickness, or different thicknesses may be used for each layer.
[0158] <Non-magnetic metal layer>
[0159] The non-magnetic metal layer is made of a metal material that is a diamagnetic or paramagnetic material. In one embodiment, although there is no particular limitation on the material of the non-magnetic metal layer used, a metal material with excellent electrical conductivity is preferred from the viewpoint of improving the shielding properties against AC magnetic fields and AC electric fields. Specifically, a metal material with an electrical conductivity of 1.0×10 6 S / m (value at 20°C. The same applies hereinafter.) or more, and the conductivity of the metal is more preferably 10.0×10 6 S / m or more, and more preferably 30.0×10 6 S / m or more, most preferably 50.0×10 6 S / m or more. As such metal, the conductivity is about 39.6×10 6 S / m aluminum, the conductivity is about 58.0×10 6 That is, the non-magnetic metal layer preferably contains at least one selected from copper, copper alloy, aluminum and aluminum alloy in consideration of both electrical conductivity and cost. These are preferred in practical use.
[0160] (Elongation at break)
[0161] From the viewpoint of formability, the elongation at break of the non-magnetic metal layer in the RD direction is preferably 2% or more, more preferably 5% or more. However, considering a reasonable elongation at break, the elongation at break in the RD direction is typically 80% or less, more typically 60% or less.
[0162] In addition, from the viewpoint of formability, the rupture elongation of the non-magnetic metal layer in the TD direction is preferably 2% or more, more preferably 5% or more. However, considering a reasonable rupture elongation, the rupture elongation in the TD direction is typically 80% or less, more typically 60% or less.
[0163] The method for measuring the elongation at break in each direction is the same as the method for measuring the elongation at break in each direction of the laminate described above.
[0164] (thickness)
[0165] The thickness of the non-magnetic metal layer is not particularly limited. From the viewpoint of shape retention, the total thickness of the non-magnetic metal layer is preferably 10 μm or more, more preferably 15 μm or more, even more preferably 20 μm or more, even more preferably 25 μm or more, and further preferably 30 μm or more. However, from the viewpoint of cost reduction, the total thickness of the non-magnetic metal layer is preferably 500 μm or less, more preferably 300 μm or less, and even more preferably 100 μm or less.
[0166] In one embodiment, from the viewpoint of shielding properties, the thickness of each non-magnetic metal layer is preferably 5 μm or more, more preferably 10 μm or more, and even more preferably 15 μm or more. However, if the thickness of each non-magnetic metal layer is too thick, the cost will increase, so it is preferably 200 μm or less, more preferably 160 μm or less, and even more preferably 100 μm or less.
[0167] It should be noted that the method for measuring the thickness of the non-magnetic metal layer is the same as the method for measuring the thickness of the laminated body described above.
[0168] In one embodiment, when a plurality of non-magnetic metal layers are formed, all non-magnetic metal layers may be formed of the same material, or different materials may be used for each layer. In addition, all non-magnetic metal layers may have the same thickness, or the thickness of each layer may be different. In addition, the treatment film described below is regarded as a part of the non-magnetic metal layer.
[0169] The shape of the non-magnetic metal layer is not particularly limited, and metal foil can be cited as an example. When copper foil is used as the metal foil, it is preferred that the purity is higher based on the viewpoint of improving the shielding properties, and the purity is preferably 99.5% by mass or more, and more preferably 99.8% by mass or more. As the copper foil, rolled copper foil, electrolytic copper foil, metallized copper foil, etc. can be used, and rolled copper foil with excellent bending properties and forming processability is preferred. In the case of adding alloy elements to the copper foil to make a copper alloy foil, the total content of these elements and unavoidable impurities is less than 0.5% by mass. In particular, when the copper foil contains a total of 50 to 5000 ppm by mass of at least one selected from tin, manganese, chromium, zinc, zirconium, magnesium, nickel, silicon and silver, and / or 10 to 50 ppm by mass of phosphorus, the elongation is increased compared to the pure copper foil of the same thickness, so it is preferred.
[0170] <Treatment film>
[0171] On the surface of one side of the non-magnetic metal layer, there may also be a treatment film of a copper-containing alloy, or on the surfaces of both sides of the non-magnetic metal layer, there may be the above-mentioned treatment film. At this time, based on the viewpoint of effectively playing the role of electromagnetic wave absorption or attenuation in the ferromagnetic layer, it is preferred that the ferromagnetic layer and the non-magnetic metal layer are arranged with the treatment film in between. The treatment film is, for example, formed on the surface of the ferromagnetic layer side of the non-magnetic metal layer adjacent to the ferromagnetic layer.
[0172] The treatment film is formed on the surface of at least one side of the non-magnetic metal layer from the viewpoint of improving the shielding characteristics. As an example, it can also include one or more selected from electromagnetic wave absorption auxiliary films of copper alloys, heat-resistant films, rust-proof films and weather-resistant films. As heat-resistant films after heat-resistant treatment, plating films and vapor-deposited films containing cobalt and nickel can be listed. As rust-proof films after rust-proof treatment, inorganic plating films and vapor-deposited films such as zinc and chromium, organic films such as benzotriazole can be listed. As weather-resistant films after silane coupling agent treatment, organic coatings containing silane coupling agents can be listed. That is, in addition to copper, the treatment film can also contain one or more metals selected from cobalt, nickel, zinc, molybdenum, tin, phosphorus, tungsten, chromium and silicon.
[0173] Note that, when the ferromagnetic layer is a composite sheet containing a resin, the treatment film interposed between the ferromagnetic layer and the nonmagnetic metal layer can also improve the adhesion between the ferromagnetic layer and the nonmagnetic metal layer.
[0174] The electromagnetic wave absorption auxiliary film can be produced by a known method, for example, by plating, metal evaporation, sputtering, etc. As an example, a method of forming an electromagnetic wave absorption auxiliary film formed of copper, an electromagnetic wave absorption auxiliary film formed of copper and nickel, or an electromagnetic wave absorption auxiliary film formed of copper, cobalt, and nickel by applying a plating process on the surface of a non-magnetic metal layer is described below.
[0175] In the plating process for forming the electromagnetic wave absorption auxiliary film, a particle film formed of copper, a particle film formed of copper and nickel, or a particle film formed of copper, cobalt and nickel is formed on the surface of at least one side of the non-magnetic metal layer.
[0176] (Plating Conditions (Roughening Plating Treatment) 1: Copper Plating)
[0177] An example of copper plating treatment conditions is as follows.
[0178] Liquid components: copper 10-23g / L, sulfuric acid 45-110g / L
[0179] Liquid temperature: 20~55℃
[0180] Current density: 10~60A / dm 2
[0181] Coulomb amount: 5~30As / dm 2
[0182] (Plating Conditions (Roughening Plating) 2: Copper and Nickel Alloy Plating)
[0183] An example of the plating treatment conditions of copper and nickel is as follows.
[0184] Liquid components: copper 10-20g / L, nickel 5-15g / L
[0185] pH: 2-3
[0186] Liquid temperature: 30~50℃
[0187] Current density: 10~65A / dm 2
[0188] Coulomb amount: 10~50As / dm 2
[0189] (Plating Conditions (Roughening Plating) 3: Copper, Cobalt, and Nickel Alloy Plating)
[0190] An example of the plating treatment conditions of copper, cobalt, and nickel is as follows.
[0191] Liquid components: copper 10-20g / L, cobalt 5-15g / L, nickel 5-15g / L
[0192] pH: 2~3
[0193] Liquid temperature: 30~50℃
[0194] Current density: 10~65A / dm 2
[0195] Coulomb amount: 10~48As / dm 2
[0196] In this case, the roughening plating treatment can be performed in multiple stages under the above-mentioned plating treatment conditions 1 to 3.
[0197] In the heat-resistant treatment, at least one of the heat-resistant films 1 to 8 described below can be formed on the electromagnetic wave absorption auxiliary film described above. The plating conditions and vapor deposition conditions are as follows.
[0198] (Plating Conditions of Heat-Resistant Film 1) (Co—Ni Plating: Cobalt-Nickel Alloy Plating)
[0199] Liquid components: nickel 5-20g / L, cobalt 1-8g / L
[0200] pH: 2-3
[0201] Liquid temperature: 40~60℃
[0202] Current density: 10~30A / dm 2
[0203] Coulomb amount: 2~20As / dm 2
[0204] (Plating Conditions of Heat-Resistant Film 2) (Ni-Zn Plating: Nickel-Zinc Alloy Plating)
[0205] Liquid components: Nickel 2-30g / L, Zinc 2-30g / L
[0206] pH: 3-4
[0207] Liquid temperature: 30~50℃
[0208] Current density: 1~10A / dm 2
[0209] Coulomb amount: 0.5~2As / dm 2
[0210] (Plating Conditions of Heat-Resistant Film 3) (Ni-Cu Plating: Nickel-Copper Alloy Plating)
[0211] Liquid components: Nickel 2-30g / L, Copper 2-30g / L
[0212] pH: 3-4
[0213] Liquid temperature: 30~50℃
[0214] Current density: 1~2A / dm 2
[0215] Coulomb amount: 1~2As / dm 2
[0216] (Plating Conditions of Heat-Resistant Film 4) (Ni-Mo Plating: Nickel-Molybdenum Alloy Plating)
[0217] Liquid composition: Ni sulfate hexahydrate: 45~55g / dm 3 , Sodium molybdate dihydrate: 50~70g / dm 3 , sodium citrate: 80~100g / dm 3
[0218] pH: 1.5~4.5
[0219] Liquid temperature: 20~40℃
[0220] Current density: 1~4A / dm 2
[0221] Coulomb amount: 1~2As / dm 2
[0222] (Plating Conditions of Heat-Resistant Film 5) (Ni—Sn Plating: Nickel-Tin Alloy Plating)
[0223] Liquid components: Nickel 2-30g / L, Tin 2-30g / L
[0224] pH: 1.5~4.5
[0225] Liquid temperature: 30~50℃
[0226] Current density: 1~2A / dm 2
[0227] Coulomb amount: 1~2As / dm 2
[0228] (Plating Conditions of Heat-Resistant Film 6) (Ni—P Plating: Nickel-Phosphorus Alloy Plating)
[0229] Liquid components: Nickel 30-70g / L, Phosphorus 0.2-1.2g / L
[0230] pH: 1.5~2.5
[0231] Liquid temperature: 30~40℃
[0232] Current density: 1~2A / dm 2
[0233] Coulomb amount: 1~2As / dm 2
[0234] (Plating Conditions of Heat-Resistant Film 7) (Ni-W Plating: Nickel-Tungsten Alloy Plating)
[0235] Liquid components: Nickel 2-30g / L, Tungsten 0.01-5g / L
[0236] pH: 3-4
[0237] Liquid temperature: 30~50℃
[0238] Current density: 1~2A / dm 2
[0239] Coulomb amount: 1~2As / dm 2
[0240] (Evaporation Conditions of Heat-Resistant Film 8) (Ni-Cr Vapor Deposition: Nickel-Chromium Alloy Vapor Deposition)
[0241] A nickel-chromium alloy vapor-deposited film is formed using a sputtering target having a composition of 65 to 85 mass % of nickel and 15 to 35 mass % of chromium.
[0242] Target: 65-85% nickel, 15-35% chromium
[0243] Equipment: Sputtering equipment manufactured by ULVAC Co., Ltd.
[0244] Power: DC50W
[0245] Argon pressure: 0.2Pa
[0246] In the rust-proof treatment, the rust-proof film and / or weather-resistant film described below can be further formed on the electromagnetic wave absorption auxiliary film or the heat-resistant film described above. The conditions are as follows.
[0247] (Rust-proof film plating conditions)
[0248] Liquid components: Potassium dichromate 1-10g / L, zinc 0.2-0.5g / L
[0249] pH: 3-4
[0250] Liquid temperature: 50~70℃
[0251] Current density: 0~2A / dm 2 (0A / dm 2 This is the case of immersion chromate treatment. )
[0252] Coulomb amount: 0~2As / dm 2 (0As / dm 2 This is the case of immersion chromate treatment. )
[0253] (Types of weather-resistant films (silane coupling films))
[0254] As an example, application of a diaminosilane aqueous solution or an epoxysilane aqueous solution can be mentioned.
[0255] It should be noted that when a metal film or a plated film such as a heat-resistant film is formed by vapor deposition (dry plating) such as sputtering, and when a metal film or a plated film such as a heat-resistant film is formed by plating (wet plating), that is, when the plated film is normally plated (smoothly plated, that is, plated with a current density less than the limiting current density), the metal film or the plated film will not affect the shape of the surface of the non-magnetic metal layer.
[0256] The limiting current density varies with metal concentration, pH, liquid supply rate, inter-electrode distance, and plating solution temperature. In the present invention, the current density at the boundary between normal plating (the plated metal is precipitated in a film form) and roughened plating (burnt plating, the plated metal is precipitated in a crystalline form (spherical, needle-shaped, frost-shaped, etc.) with bumps and depressions) is defined as the limiting current density, and the current density that becomes the limit of normal plating (just before becoming burnt plating) in the Hall cell test (visual judgment) is used as the limiting current density.
[0257] Specifically, metal concentration, pH, and plating solution temperature are set as the manufacturing conditions of plating, and the Hall slot test is performed. Then, the metal layer formation state (whether the metal of the plating is formed in a layered state or in a crystalline state) under the plating solution component and the plating solution temperature is investigated. In addition, based on the current density quick-check table manufactured by Yamamoto Gold Plating Tester Co., Ltd., according to the position of the sample at the boundary of the normal plating and the roughening plating of the sample, the current density of the position of the boundary is obtained. Then, the current density of the position of the boundary is defined as the limiting current density. Thus, it can be known that the boundary current density under the plating solution component and the plating solution temperature. Usually, if the inter-electrode distance is short, there is a tendency for the boundary current density to increase.
[0258] The method of the Hall cell test is described, for example, in "Plating Practical Reading" written by Maruyama Kiyoshi and published by Nikkan Kogyo Shimbun on June 30, 1983, pages 157 to 160.
[0259] It should be noted that in order to perform the plating treatment at a current density lower than the limiting current density, the current density during the plating treatment is preferably 20 A / dm 2 Below, more preferably 10A / dm 2 Below, more preferably 8A / dm2 the following.
[0260] Furthermore, since the thickness of the rust-proof film and the weather-resistant film is very thin, they do not affect the shape of the surface of the non-magnetic metal layer.
[0261] (Shielding characteristics)
[0262] According to one embodiment, at 0.1MHz, it can have a magnetic field shielding characteristic of 1dB or more (how much signal attenuation there is on the receiving side), preferably it can have a magnetic field shielding characteristic of 5dB or more, more preferably it can have a magnetic field shielding characteristic of 10dB or more, and more preferably it can have a magnetic field shielding characteristic of 15dB or more, and further preferably it can have a magnetic field shielding characteristic of 18dB or more. In the present invention, the magnetic field shielding characteristic can be measured by the KEC method. The KEC method refers to the "Electromagnetic Wave Shielding Characteristics Measurement Method" of the Kansai Electronic Industry Promotion Center.
[0263] (use)
[0264] In one embodiment, in particular, it can be used for covering materials or exterior materials for electrical equipment or electronic equipment (for example, inverters, communication machines, resonators, electron tubes / discharge lamps, electrical heating equipment, motors, generators, electronic components, printed circuits, mechanical equipment, etc.), covering materials for wiring harnesses and communication cables connected to electrical equipment or electronic equipment, electromagnetic wave shielding sheets, electromagnetic wave shielding plates, electromagnetic wave shielding bags, electromagnetic wave shielding boxes, electromagnetic wave shielding rooms, and other various electromagnetic wave shielding purposes.
[0265] [Example]
[0266] The present invention will be specifically described based on Examples, Comparative Examples and Reference Examples. The following Examples, Comparative Examples and Reference Examples are only specific examples given to facilitate understanding of the technical content of the present invention, and the technical scope of the present invention is not limited to these specific examples.
[0267] It should be noted that, in Tables 1 and 2, “resin layer” corresponds to “non-magnetic resin layer”, “metal layer” corresponds to “non-magnetic metal layer”, and “magnetic layer” corresponds to “ferromagnetic layer”, respectively.
[0268] [Discussion of Materials]
[0269] (Reference Examples 1 to 8)
[0270] First, in Reference Examples 1 to 8, various materials as shown below were prepared, and the shape retention, elongation at break, shielding properties, and anisotropy values of various materials at break were measured. The results are shown in Table 1. It should be noted that the RD direction of the magnetic layer 1 and the magnetic layer 2 refers to the length direction of the A4 sample, and the TD direction refers to the width direction. The measurement conditions and evaluation criteria are as follows. The "-" mark in Table 1 indicates that even if the measurement is performed, no numerical value can be obtained or no measurement is performed.
[0271] In addition, the resin layers 1 to 3, the bonding layer 1, the metal layers 1 to 2, and the magnetic layers 1 to 2 in Tables 1 and 2 are as follows.
[0272] Resin layer 1: PET film (thickness 98 to 103 μm, EMBLET SD100, manufactured by UNITIKA)
[0273] Resin layer 2: Teflon (registered trademark) sheet (thickness 99 μm, NITOFLON, manufactured by Nitto Denko)
[0274] Adhesive layer 1: Adhesive (thickness 18 μm, RU-80, manufactured by Rockpaint)
[0275] Resin layer 3: Teflon (registered trademark) sheet (thickness 99 μm, NITOFLON, manufactured by Nitto Denko) having an adhesive (thickness 18 μm, RU-80, manufactured by Rockpaint) on one surface
[0276] Metal layer 1: rolled copper foil (thickness 17.5 μm (nominal value), manufactured by JX Metal)
[0277] Metal layer 2: rolled copper foil (thickness 18 μm (nominal value), manufactured by JX Metal)
[0278] Magnetic layer 1: composite sheet (thickness 90 to 96 μm, GM010S, manufactured by Takeuchi Industries, relative magnetic permeability at a frequency of 1 MHz is about 24 (from the table in the product catalog))
[0279] Magnetic layer 2: composite sheet (thickness 43-48 μm, P100NH, manufactured by Takeuchi Industries, relative magnetic permeability at a frequency of 1 MHz is about 130 (from the table in the product catalog))
[0280] (Shape retention)
[0281] For each material of Reference Example 1 and Reference Examples 5 to 8, a molded body was produced at room temperature (approximately 22 to 26° C.) according to the following procedure in order to evaluate the shape retaining property.
[0282] (1) Figure 1Various materials are clamped between the die and the clamp of the processing machine shown in (A).
[0283] (2) Figure 1 As shown in (B), the punch is moved vertically downward along the die and the clamp and pressed into the punch hole. It should be noted that the spacing between the die and the punch is set to 0.5 mm. The moving distance of the punch without cracks on the surface of the molded body when molding various materials is used as the moldable stroke shown in Table 1. It should be noted that the stroke starts from 3 mm, and the movement amount is increased by 1 mm each time to mold and confirm the appearance of the molded body. In the case of material cracks in the molded body molded at 3 mm, the moldable stroke is recorded as 0.
[0284] (3) Figure 1 As shown in (C), the punch is moved vertically upward and returned to its original position. Thus, a molded body having a bottomed shape can be obtained.
[0285] (4) The obtained molded body can be measured using a confocal microscope (ONE-SHOT 3D VR-5000, manufactured by KEYENCE) at room temperature (approximately 22 to 26°C) on the second day after molding (after more than 12 hours). The molding height of the molded body can be measured by measuring the shortest distance in the vertical direction from the height position of the surface on the clamping side of the molded body clamped by the punch and the clamping member to the height position of the inner surface of the bottom.
[0286] Through the above steps, the ratio (B / A) of the "molding height (B) of the molded body" to the obtained "molding stroke (A)" is calculated.
[0287] Comprehensive judgment
[0288] The case where the ratio (B / A) was 75% or more was evaluated as "0", the case where the ratio (B / A) was 50% or more and less than 75% was evaluated as "△", and the case where the ratio (B / A) was less than 50% was evaluated as "×". The results are shown in Table 1.
[0289] (Elongation at break)
[0290] For each material of Reference Example 1 and Reference Examples 4 to 8, the elongation at break in the RD direction and / or TD direction was measured. The elongation at break was measured by the method described above at room temperature (approximately 22 to 26° C.). The results are shown in Table 1.
[0291] (Shielding characteristics)
[0292] The shielding properties of various materials in reference examples 1 to 8 were measured respectively. First, during the measurement, the outer periphery of various materials was fixed with tape in a manner that would not cause positional displacement. For various materials, the magnetic field measuring fixture of the KEC method shielding effect measuring device (manufactured by Technoscience, JSE-KEC) and the network analyzer (manufactured by Keysight Technologies, E5080) and amplifier (manufactured by ANRITSU MH648A) were used to evaluate the magnetic field shielding properties at a frequency of 0.1 MHz by the KEC method at room temperature (approximately 22 to 26°C). The results are shown in Table 1.
[0293] Comprehensive judgment
[0294] The magnetic boundary shielding characteristic value at 0.1 MHz was evaluated as "0" when it was 10 dB or more, "△" when it was 1 dB or more and less than 10 dB, and "×" when it was less than 1 dB. The results are shown in Table 1.
[0295] (Anisotropy at rupture)
[0296] The anisotropy values at break were measured for each of the materials of Reference Examples 1 to 8. The anisotropy values at break were measured by the method described above at room temperature (approximately 22 to 26° C.). The results are shown in Table 1.
[0297]
Table 1
[0298]
[0299] (Reference example examination)
[0300] Regarding the resin layer 3 having the bonding layer 1 on the resin layer 2, the Rc value is almost unchanged compared to the resin layer 2. Since the Rc value of the resin layer 1 is substantially the same as the Rc value of the resin layer 2, it can be considered that even if the Rc value of the resin layer having the bonding layer 1 provided on the resin layer 1 is measured, the same tendency can be seen. In addition, it can be inferred that even in the case of having a bonding layer on the non-magnetic resin layer, the Rc value is hardly affected. Furthermore, as shown in reference examples 7 and 8, when the Rc value is greater than 0 and less than 1, although molding with a molding stroke of 3 mm is achieved, the proportion related to shape retention is less than 50%, and it can be confirmed that the shape retention is deteriorated.
[0301] [Production of electromagnetic wave shielding materials]
[0302] (Examples 1 to 13, Comparative Examples 1 to 3)
[0303] Next, as Comparative Example 1, a commercially available electromagnetic wave shielding material was prepared to prepare a laminate 1, and shape retention, elongation at break, shielding properties, and anisotropy at break were measured in the same manner as in the reference example. The results are shown in Table 2. The structure of the laminate 1 is as follows.
[0304] Laminated body 1: Magnetic shielding sheet (thickness 120 μm, FM SHIELD (registered trademark), manufactured by Hitachi Metals)
[0305] According to the product catalog, the laminate 1 is laminated in the order of resin layer (PET film (thickness 25 μm)) / adhesive (hot melt adhesive (thickness 25 μm)) / magnetic layer 3 (thickness 18 μm, FINEMET (registered trademark), manufactured by Hitachi Metals, relative magnetic permeability at a frequency of 1 MHz is about 5000 (from the table in the product catalog)) / adhesive (hot melt adhesive (thickness 25 μm)) / resin layer (PET film (thickness 25 μm)). That is, the laminate 1 has a structure of non-magnetic resin layer / ferromagnetic layer / non-magnetic resin layer.
[0306] In addition, in Examples 1 to 13 and Comparative Examples 2 to 3, the materials of Reference Examples 1 to 8 and the bonding layer 2 shown below were appropriately combined to produce an electromagnetic wave shielding material. Then, in Examples 1 to 13 and Comparative Examples 2 to 3, the shape retention or elongation at break, shielding characteristics, and anisotropy values at break were measured in the same manner as in the reference examples. The results are shown in Table 2. The areas of the bonding surfaces of the resin layer 1, the metal layers 1 to 2, and the magnetic layers 1 to 2 are the same, and they are stacked in a manner that does not expose each other. In the example of using a PET film of the resin layer 1 and a copper foil of the metal layer 1, an adhesive (two-component urethane resin adhesive, main agent: RU80, curing agent: H-5, manufactured by rockpaint) is applied to the bonding surface of the PET film by a bar coater. In this case, one resin layer is composed of a laminate of a PET film and a bonding layer. In addition, in the magnetic layers 1 to 2, the resin layer 1 or the metal layer 1 or the metal layer 2 is bonded to the outer surface of the bonding layer that has been formed. The bonding layer 2 is described below.
[0307] Adhesive layer 2: Adhesive (thickness 4.5 μm, RU-80, manufactured by Rockpaint) [Table 2]
[0308]
[0309] (Examination of Examples and Comparative Examples)
[0310] In Examples 1 to 13, the shape retention is excellent and the shielding properties are also good. Therefore, in Examples 1 to 13, it can be said that the electromagnetic wave shielding material including a laminate having a non-magnetic resin layer, a non-magnetic metal layer and / or a ferromagnetic layer, and the value of the anisotropy (Rc) at break represented by the following formula (1) is less than 0 or greater than 1, and this electromagnetic wave shielding material is useful.
[0311] In addition, metals other than copper can be used as the non-magnetic metal layer. However, since aluminum has lower tensile strength than copper and is easily deformed, it is presumed that the same effect of improving formability can be obtained by lamination.
[0312] In particular, by laminating the nonmagnetic resin layer, the nonmagnetic metal layer, and the ferromagnetic layer using one or more layers respectively, the shielding characteristics at 0.1 MHz can be made to be 10 dB or more, and a laminated body which is also an excellent electromagnetic wave shielding material can be obtained.
[0313] On the other hand, no molded body could be produced in Comparative Examples 1 to 3. Analyzing the results of Comparative Examples 1 to 3 and Reference Examples 1 to 8, it is estimated that when the anisotropy (Rc) value at break is not less than 0 or greater than 1, it is not possible to obtain an electromagnetic wave shielding material having excellent shape retention.
Claims
1. An electromagnetic wave shielding material comprising a laminate, wherein the laminate has: a non-magnetic resin layer, and a non-magnetic metal layer and / or a ferromagnetic layer, wherein: The value of the anisotropy (Rc) at the time of rupture represented by the following formula (1) is 0 or less or 1 or more: Rc: Anisotropy at rupture w: Width of the fractured portion of the laminate after tensile test (mm) w0: Width of the laminate before tensile test (mm) t: Thickness of the broken part of the laminate after the tensile test (μm) t0: thickness of the laminate before the tensile test (μm).
2. The electromagnetic wave shielding material according to claim 1, wherein The laminated body comprises the non-magnetic metal layer. The non-magnetic resin layer is provided on surfaces of both sides of the non-magnetic metal layer.
3. The electromagnetic wave shielding material according to claim 1 or 2, wherein: The laminated body comprises the ferromagnetic layer. The non-magnetic resin layer is provided on both sides of the ferromagnetic layer.
4. The electromagnetic wave shielding material according to any one of claims 1 to 3, wherein The non-magnetic metal layer has a thickness of 10 to 200 μm and contains at least one metal having a rupture elongation of 2% or more in the RD direction.
5. The electromagnetic wave shielding material according to any one of claims 1 to 4, wherein The nonmagnetic metal layer contains at least one selected from copper, copper alloys, aluminum, and aluminum alloys.
6. The electromagnetic wave shielding material according to any one of claims 1 to 5, wherein The value of the anisotropy (Rc) of the non-magnetic resin layer at the time of rupture represented by the following formula (2) is 1.0 or more and 10 or less, or -10 or more and o or less: Rc: Anisotropy at rupture w: Width of the fractured portion of the non-magnetic resin layer after the tensile test (mm) w0: Width of the non-magnetic resin layer before the tensile test (mm) t: Thickness of the fractured portion of the non-magnetic resin layer after the tensile test (μm) t0: thickness of the non-magnetic resin layer before the tensile test (μm).
7. The electromagnetic wave shielding material according to any one of claims 1 to 6, wherein The non-magnetic resin layer contains at least one selected from PET and PC.
8. The electromagnetic wave shielding material according to any one of claims 1 to 7, wherein The non-magnetic resin layer contains conductive particles and / or conductive fibers. 9 . A covering material or an exterior material for an electric device or an electronic device, comprising the electromagnetic wave shielding material according to claim 1 .
10. An electric device or an electronic device comprising the covering material or the exterior material according to claim 9.
Citation Information
Patent Citations
Noise suppression sheet and laminate
JP2021028940A